ANALISIS PENGARUH STOCK SPLIT DAN KINERJA KEUANGAN TERHADAP HARGA SAHAM STUDI PADA EMITEN SEKTOR MANUFAKTUR - S Sukimin (Universitas Mercu Buana, 2017)
Stock split is one of the corporate action by the company with the goal set back to stock prices in the range that is more liquid and provide a quality signal to investors. This study aims to analyze the effect of the stock split and the financial performance of the issuer's stock price studies on the manufacturing sector. The theory is the reference of this study, namely Signaling Theory. Signaling theory declares a stock split provides a positive signal for the company manager will inform the future prospects of the company to the public good who do not know. The stock price is the value of a stock that reflects the wealth of the company that issued the stock. Stock prices are formed from the interaction of buyers and sellers of shares in the stock market or stock exchange which is motivated by their expectations of corporate profits. The study was conducted on 7 companies that are listed on the Stock Exchange and they do stock split in the year 2008-2011. Hipoteis testing in this study using multiple regression. The research instrument will be tested in this study is the Earning Per Share (EPS), Return On Investment (ROI), Return on Equity (ROE), Price Earning Ratio (PER), Price to Book Value (PBV) is to test the effect of the stock split and financial performance of the company's stock price. The equations are formed in this study is Stock Price = C + 11,18421EPS - 2,10ROI - 23,62ROE + 556,82PBV + 85,25PER - 244,80Stocksplit + e. The results showed Earning Per Share (EPS) is a variable financial performance and a significant positive effect on stock prices, both before and after stocksplit, while the Return On Investment (ROI), Return on Equity (ROE), Price Earning Ratio (PER), Price to Book Value (PBV) effect is not significant. According to the theory, the higher the ratio of financial performance, the better the state of a company